TEXNOLOGIYA TA’LIMI FANINI AMALIY О‘QITISHNING INNOVATSION TASHKILIY-METODIK JIHATLARI - Ochilov, A.O. (SCIENCE and SOCIETY, 2024)
The article presents information about the theoretical foundations of teaching the subject “Methodology of teaching technological education” to students studying in the field of technological education, as well as about general organizational and methodological methods of practical vocational education. In addition, virtual laboratory work related to the content and stages of education, work performed in educational workshops, production, and are covered the formation of components of the integrative structure of professional practice.